2016
DOI: 10.14236/jhi.v23i1.185
|View full text |Cite
|
Sign up to set email alerts
|

Designing Patient-facing Health Information Technologies for the Outpatient Settings: A Literature Review

Abstract: The designs of patient-facing HITs in outpatient settings are promising in facilitating the doctor-patient communication and patient engagement. However, their effectiveness and usefulness need to be further evaluated and improved from a systems perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(111 reference statements)
1
7
0
Order By: Relevance
“…6 Current designs might be problematic even in the more sheltered environment of an outpatient clinic and might require separate evaluation. 12 Like others, we observed how electronic systems can aid to enhance communication between patients and healthcare professionals but might move focus from the patient to the screen and reduce eye contact. 13 Recording of urgent information was slowed down by the electronic system.…”
Section: Discussionsupporting
confidence: 68%
“…6 Current designs might be problematic even in the more sheltered environment of an outpatient clinic and might require separate evaluation. 12 Like others, we observed how electronic systems can aid to enhance communication between patients and healthcare professionals but might move focus from the patient to the screen and reduce eye contact. 13 Recording of urgent information was slowed down by the electronic system.…”
Section: Discussionsupporting
confidence: 68%
“…While this educational intervention targeted patients, it is also important to teach patient-centered EHR behaviors to physicians to promote patient-physician-EHR engagement [ 20 - 26 , 58 , 59 ], and these efforts should be pursued in tandem. Additionally, EHRs should evolve to account for user experience, patient health literacy levels, and language needs to help reduce the digital divide and health disparities [ 19 , 60 - 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this educational intervention targeted patients, it is also important to teach patient-centered EHR behaviors to physicians to promote patient-physician-EHR engagement [20][21][22][23][24][25][26]58,59], and these efforts should be pursued in tandem. Additionally, EHRs should evolve to account for user experience, patient health literacy levels, and language needs to help reduce the digital divide and health disparities [19,[60][61][62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the impact of EHR use have found that certain physician behaviors (eg, poor eye contact, long silences) may lead to decreased patient satisfaction with the patient-physician relationship and communication [4][5][6][7][8][9][10][11]. While studies show there are certain patient-centered care behaviors that can positively impact patient satisfaction and health outcomes, with Table 1 serving as a model for incorporating many evidence-based behaviors, physicians are faced with the challenge of staying focused on their patients while efficiently navigating the EHR during clinical encounters [4,6,[12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%